Peran Santri dalam Mewujudkan Indonesia Emas 2045 “Menelisik peranan santri milenial dalam kontek kekinian” - Zulkifli Zulkifli; M. Khatami (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2022)
Through Presidential Decree No. 15 of 2015, students are recorded as history who have played a major role in Indonesian independence. Therefore, October 22 was designated as a santri day led by KH Hasyim Asy'ari for jihad against the Dutch colonialists. It was this spirit that sparked the ferocious resistance on November 10 and the departure of the Dutch from Indonesia. Along with its development, a new term emerged which became the subject of discussion among Islamic boarding schools, namely millennial santri. Millennial Santri is a generation that has jumped far beyond the reach of its predecessors but has not lost its identity as a Santri. With all the characteristics they have, millennial students have occupied a separate point of view in the hearts of Indonesian people. Now the role of millennial students with their predecessors. Millennial students play an active role as promoters and creatively respond to the times. In addition to millennial students who are diligent in reciting the Koran, pursuing Islamic studies, serving teachers, they must also be literate in ICT developments and capable of playing their role (as the author has described above). It is hoped that millennial students can help in realizing a golden Indonesia 2045